Magnesium sulfate protects oligodendrocyte lineage cells in a rat cell-culture model of hypoxic–ischemic injury. (May 2016) - Itoh, Kanako; Maki, Takakuni; Shindo, Akihiro; Egawa, Naohiro; Liang, Anna C.; Itoh, Naoki; Lo, Eng H.; Lok, Josephine; Arai, Ken
Highlights: Magnesium-sulfate-exposed oligodendrocytes exhibited more resistance to hypoxic–ischemic injury. Magnesium sulfate accelerated the differentiation step of oligodendrocyte lineage cells. Magnesium sulfate did not directly protect mature oligodendrocytes against hypoxic–ischemic damage. Abstract: Hypoxic–ischemic (HI) brain injury in newborns results in serious damage. Magnesium sulfate has been clinically used as a cyto-protective agent against HI brain injury in newborns in some countries, including Japan. However, it is not clear how magnesium exerts this effect and how it acts on the individual types of cells within the newborn brain. In this study, we exposed cultured rat oligodendrocyte precursor cells to magnesium sulfate during the period when they differentiate into oligodendrocytes, and showed that magnesium-exposed oligodendrocytes exhibited more resistance to HI injury. Our data may support the use of magnesium sulfate in the clinical setting.